Ocean circulation and sea‐ice thinning induced by melting ice shelves in the Amundsen Sea. Issue 3 (30th March 2017) - Jourdain, Nicolas C.; Mathiot, Pierre; Merino, Nacho; Durand, Gaël; Le Sommer, Julien; Spence, Paul; Dutrieux, Pierre; Madec, Gurvan
Abstract: A 1/12° ocean model configuration of the Amundsen Sea sector is developed to better understand the circulation induced by ice‐shelf melt and the impacts on the surrounding ocean and sea ice. Eighteen sensitivity experiments to drag and heat exchange coefficients at the ice shelf/ocean interface are performed. The total melt rate simulated in each cavity is function of the thermal Stanton number, and for a given thermal Stanton number, melt is slightly higher for lower values of the drag coefficient. Sub‐ice‐shelf melt induces a thermohaline circulation that pumps warm circumpolar deep water into the cavity. The related volume flux into a cavity is 100–500 times stronger than the melt volume flux itself. Ice‐shelf melt also induces a coastal barotropic current that contributes 45 ± 12% of the total simulated coastal transport. Due to the presence of warm circumpolar deep waters, the melt‐induced inflow typically brings 4–20 times more heat into the cavities than the latent heat required for melt. For currently observed melt rates, approximately 6–31% of the heat that enters a cavity with melting potential is actually used to melt ice shelves. For increasing sub‐ice‐shelf melt rates, the transport in the cavity becomes stronger, and more heat is pumped from the deep layers to the upper part of the cavity then advected toward the ocean surface in front of the ice shelf. Therefore, more ice‐shelf melt induces less sea‐ice volume near the ice sheet margins. Plain Language Summary: The ice‐shelf cavities of the Amundsen Sea, Antarctica, act as very powerful pumps that create strong inflows of warm water under the ice‐shelves, as well as significant circulation changes in the entire region. Such warm inflows bring more heat than required to melt ice, so that a large part of that heat exits ice‐shelf cavities without being used. Due to mixing between warm deep waters and melt freshwater, melt‐induced flows are warm and buoyant when they leave cavities. Therefore, they reach the ocean surface near ice‐shelf fronts and can melt significant amounts of sea ice. It is thus suggested that climatic trends in sub ice‐shelf melt could partly explain sea ice trends near the ice‐sheet margins in the Amundsen Sea region. Key Points: Amundsen Sea ice‐shelves melt induces circulations into/out of ocean cavities, 100–500 times stronger than net meltwater flows These circulations bring 4–20 times more heat into cavities than is required for melt Ice shelves act as important pumps upwelling heat from deep layers to the surface and decreasing sea‐ice volume in their vicinity